Synthesis and Physicochemical Properties of Purple Clay - KOURIM Aicha; MALOUKI Moulay Abderrahmane; ZIOUCHE Aicha; BOULAHBAL Mouna; MOKHTARI Madjda (University Of Eloued جامعة الوادي, 2020)
Natural clays are very abundant, eco-friendly, and available materials for depollution. Over the recent years, these natural resources and their modified forms are used as low-cost adsorbents in the removal or pollutants. This paper describes the variations of physicochemical properties values of pH, the specific surface area, the point of zero charge and the cation exchange capacity between natural clay and its composites.
Intervention
Keywords: Clay; modified-clay; physicochemical properties